Analisis Pupuk Organik Cair Limbah Industri Tahu Dan Air Cucian Beras - Sukmawati Sukmawati; Sufi Ainun Nisa; Ardian Desta Pratama; Fadli Nur Fauzi (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2022)
Domestic waste contains good organic matter for plant growth. One of the domestic wastes owned by each house is rice washing water. In addition, the tofu industry is also widely found in Indonesia, one of which is Cilacap City. The content of organic matter possessed by the two wastes is a source of plants. To reduce the environment, this waste can be used as raw material for making liquid organic fertilizer (POC). In addition to being environmentally friendly, the raw materials used are also easy to find. This study aims to analyze pH, temperature and levels of C-Organic in liquid organic fertilizer from tofu industrial waste and rice washing water. The manufacture of liquid fertilizer is carried out using the anaerobic method, which utilizes bacteria that are active without oxygen through a fermentation process for 14 days. To determine the effect of adding EM4 and molasses, compositional variations were carried out on samples of liquid fertilizer, namely KO, P1, P2, and P3 with molasses volume sequentially 0 grams, 5 grams, 5 grams, 10 grams. Meanwhile, the volume of EM4 added sequentially is 0%, 5%, 10% and 5%. Measurements of pH and temperature were carried out every 4 days, but measurements of C-Organic were carried out at the beginning and end of the mini-research. The final pH of POC was in accordance with quality standards with KO = 4.5 and P1, P2 and P3 = 4. The final temperature of KO samples was 29.5ᵒC, P1 29ᵒC, P2 and P3 28.5ᵒC. The highest organic-C content was owned by the knockout sample, which was 0.00297. All samples in this mini research are not included in liquid organic fertilizer (POC) but can be classified as nutrients for soil improvement.